Biomechanical effects of non-specific low back pain kneading manipulation in TCM based on surface electromyography technology - Du, Jiong; Yang, Qi; Wang, Shihao; Zhao, Yongfang; Tian, Tianning (Molecular & cellular biomechanics, 2025)
Background: Non-specific back pain (NLBP) is one of the common musculoskeletal disorders, which can seriously affect the patient’s life. As one of the methods for treating low back pain, the kneading manipulation in TCM has shown unique advantages in relieving muscle tension and pain. Method: 70 NLBP patients were selected as the research subjects. The surface electromyography technology was used to test hardness value, pain value, surface electromyography during complete flexion, surface electromyography during dorsiflexion, and flexion extension ratio. Result: The hardness value before treatment was 47.84% ± 4.33%, which decreased to 44.56% ± 4.08% after treatment, with a P-value of 0.0017, indicating a significant effect of treatment on reducing hardness values. The average pain threshold before treatment was 25.45 ± 5.23 N. After treatment, the pain threshold increased to 26.78 ± 4.08 N, with a P-value of 0.2397, demonstrating that the treatment effect on pain values was not significant. Conclusion: The study reveals the therapeutic effect and mechanism of action of the kneading manipulation in TCM on NLBP patients. It is expected to provide scientific basis for the application of the kneading manipulation in TCM technique in the treatment of NLBP, and provide reference for optimizing treatment plans and improving efficacy